MISA TRADISIONAL MENURUT MOTU PROPRIO TRADITIONES CUSTODES - Karundeng, Federicoh; Dedha, Fransiskus Xaverius; Oroh, Aristi Vanessa (Pineleng Theological Review, 2024)
Liturgy is an expression of faith in God which is expressed in a great way through the Eucharistic Celebration. Before the Second Vatican Council, the Church celebrated the Liturgy by using the 1962 Roman Missal, or celebrating the Traditional Mass (Tridentine). After the implementation of the Second Vatican Council, it was mutually agreed that the expression of Faith through the liturgy, using the 1970 Roman Missal, which was issued by Pope Paul Vi. Since then, the practice of using traditional mass is rarely used anymore. During the Pontifical period of Pope Benedict XVI, he issued the Motu Proprio Summorum Pontificum, which permitted the Return to the Practice of this Traditional Mass. Three years later, Pope Francis asked the bishops through the Congregation for the Doctrine of the Faith to review the implementation of the Summorum Pontificum. The Pope discovered that there was a movement towards division, so Pope Francis issued the Motu Proprio Traditionis Custodes to cancel the existing norms and laws in the Summorum Pontificum, to maintain the unity of the Church.